Strategic Planning Related to Expand Income Tax Basis of the Income Tax Department: A Field Study on the Income Tax Departments in Palestine - Alkababji, Majdi; Alhimony, Sandy (The Arab Journal of Administration, 2022)
The purpose of this study is to identify the relationship between strategic planning and broadening the tax base, through measuring the practice of strategic planning in the income tax departments, and the means of broadening the tax base. In order to achieve the objectives of the study the researchers have designed a questionnaire that was distributed to all income tax officials in the West Bank, who have already obtained the permission of tax estimator who are (135) officials, (96) valid statistical analysis were recovered. The results showed that the degree of strategic planning in income tax is medium. And that there is a direct correlation between (analysis of the external environment, internal environment analysis, strategic objectives, strategic plan) and broadening the tax base proxy by (reducing tax evasion, reduce and simplify the procedures, encourage voluntary compliance, increased the receipt of custom to the public treasury, tax awareness), And also, that there is no statistical relationship between vision and mission and broadening the tax base. The researchers have presented a set of recommendations including: General management should adhere to income tax preparing strategic plans and without linking it to external funding, and providing advanced information systems that contribute to the formation of a database established for the strategic planning process (external environment, internal environment), to provide potentials and resources that are essential to the implementation of the strategic planning in addition to paying attention to aspects of implementation and control over strategic plans, the strategic plan should include detailed mechanisms and specific also a clear framework Schedule and monitor their implementation to expand the tax base by reducing tax evasion, reduce and simplify the procedures, encourage voluntary compliance, tax awareness.